UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETIL ASETAT DAUN BINAHONG (Anredera scandens (L.) Moq.) TERHADAP Shigella flexneri BESERTA PROFIL KROMATOGRAFI LAPIS TIPIS - Lilies Kusuma Wardhani; Nanik Sulistyani (Universitas Ahmad Dahlan, 2012)
Antibacterial compounds that can be used for the treatment of infections caused by bacteria. Traditionally, Anredera scandens is one of plant used as traditional medicine. The aims of this research are to find out the antibacterial activity of ethyl acetate extract of Anredera scandens leaf and Minimum Bactericidal Concentration (MBC) against Shigella flexneri and to identify the chemical subtances of the ethyl acetate extract found in Anredera scandens. The Anredera scandens leaf was extracted by use of maseration method using ethyl acetate as solvent. The antibacterial assay was done using liquid dilution method with varied concentration of Anredera scandens (8,5%, 8%, 7,5%, 7%, 6,5%, 6%, 5,5%, dan 5% w/v) to determine MBC. Chromatography test was done to identify the chemical substances of Anredera scandens extract. The result of this research showed that the MBC of Anredera scandens leaf extract was 8% w/v. The result of the phytochemical screening with tube test and thin layer chromatogram showed that the extract of Anredera scandens leaf contained, polyphenols, and saponin.